Analisis Proksimat Abon Bonggol Pisang Dengan Fortifikasi Tepung Tempe Dan Lesitin - Rini Rahayu Sihmawati; Dwi Agustiyah Rosida (FMIPA : Universitas PGRI Adi Buana, 2020)
The aim of this research was to evaluate a proximate test (protein, fat, water content and carbohydrate) shredded banana corm with tempeh flour and lechitin fortification. This research is an experimental study using a completely randomized design factorial pattern. The first treatment was: Tempe soybean flour (T) with a level of T1 (5%), T2 (10%) and T3 (15%). The second treatment was lecithin (L) with levels of L1 (3%), L2 (5%) and L3 (7%) so that 9 treatment combinations were obtained. The collected data were analyzed with a 2-way classification variance test (analysis of variance). If there is a difference between treatments followed by LSD test. Proximate test results on the protein content of shredded banana corm showed that the addition of tempeh flour (T) had a very significant effect on protein content (P <0.01), while the addition of lecithin (L) was not significant (P> 0.05) both tempeh flour and lechitin did not significant on fat content and water content (P> 0.05). Tempeh flour (T) has a very significant effect on carbohydrate content (P <0.01), while the addition of lecithin (L) is not significant (P> 0.05). Keywords: banana corn, shredded, tempeh flour, lecithin, proximate test